Crime and Immigration: Evidence from Large Immigrant Waves - Brian Bell; Stephen Machin; Francesco Fasani (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2010)
This paper examines the relationship between immigration and crime in a setting where large migration flows offer an opportunity to carefully appraise whether the populist view that immigrants cause crime is borne out by rigorous evidence. We consider possible crime effects from two large waves of immigration that recently occurred in the UK. The first of these was the late 1990s/early 2000s wave of asylum seekers, and the second the large inflow of workers from EU accession countries that took place from 2004. A simple economics of crime model, when dovetailed with facts about the relative labour market position of these migrant groups, suggests net returns to criminal activity are likely to be very different for the two waves. In fact, we show that the first wave led to a small rise in property crime, whilst the second wave had no such impact. There was no observable effect on violent crime for either wave. Nor were immigrant arrest rates different to natives. Evidence from victimization data also suggests that the changes in crime rates during the immigrant waves cannot be ascribed to crimes against immigrants. Overall, our findings suggest that focusing on the limited labour market opportunities of asylum seekers could have beneficial effects on crime rates.
Keywords: F22; K42; 330; crime; immigration